2012
DOI: 10.1016/j.lungcan.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Successful erlotinib rechallenge for leptomeningeal metastases of lung adenocarcinoma after erlotinib-induced interstitial lung disease: A case report and review of the literature

Abstract: The most serious adverse reaction associated with treatment with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) is drug-induced interstitial lung disease (ILD). Because EGFR-TKIs are key drugs for patients with non-small cell lung cancer who have somatic activating mutations of the epidermal growth factor receptor gene (EGFR mutations), several cases of retreatment with EGFR-TKIs after ILD induced by these drugs have been reported. Here, we present a 68-year-old man with lung adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…4 Recent reports describe the safety and efficacy of EGFR-TKI retreatment, even after EGFR-TKI-induced ILD, and imply the need for steroid pretreatment to reduce ILD recurrence. 5 In case of crizotinib, there have not been any previous reports on the retreatment after crizotinib-induced ILD. Thus, dexamethasone was used in our case after the example of EGFR-TKI retreatment.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent reports describe the safety and efficacy of EGFR-TKI retreatment, even after EGFR-TKI-induced ILD, and imply the need for steroid pretreatment to reduce ILD recurrence. 5 In case of crizotinib, there have not been any previous reports on the retreatment after crizotinib-induced ILD. Thus, dexamethasone was used in our case after the example of EGFR-TKI retreatment.…”
Section: Discussionmentioning
confidence: 99%
“…5, 6 Furthermore, EGFR deletion 19 mutations may be predictive for improved outcomes for leptomeningeal metastasis as suggested by a recent cohort study that demonstrated that patients with EGFR deletion 19 mutations have improved clinical outcomes when compared to EGFR exon 21 mutation and EGFR wild-type cohorts with leptomeningeal metastasis. Median time to progression or symptom deterioration for patients with leptomeningeal metastasis was 7.8 months in the exon 19 deletion subgroup compared to 0.9 and 1.9 months in the wild type and exon 21 mutation cohorts, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While the average mortality rate of all 70 cases was 44.3%, that of 20 DAD pattern cases was 75%. DAD pattern was never seen in radiological images reported in successful EGFR-TKI rechallenge [ 4 ]. Both ILDs in the present case also have diffuse ground glass opacity suggesting non-DAD pattern.…”
Section: Discussionmentioning
confidence: 99%